2020
DOI: 10.1111/cge.13804
|View full text |Cite
|
Sign up to set email alerts
|

A homozygous pathogenic variant in SHROOM3 associated with anencephaly and cleft lip and palate

Abstract: Neural tube defects (NTD) are among the most common congenital anomalies, affecting about 1:1000 births. In most cases, the etiology of NTD is multifactorial and the genetic variants associated with them remain largely unknown. There is extensive evidence from animal models over the past two decades implicating SHROOM3 in neural tube formation; however, its exact role in human disease has remained elusive. In this report, we present the first case of a human fetus with a homozygous loss of function variant in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
1
10
0
1
Order By: Relevance
“…The differences in cell behaviors we observed between anterior and posterior neural ectodermal regions reflect the region-specific nature of NTDs in both humans and animal models. To explore the relationships in more detail, we next turned to loss-of-function manipulation of shroom3, which is implicated in human NTDs and has variably penetrant effects on anterior and posterior neural tube closure, (Deshwar et al, 2020;Haigo et al, 2003;Hildebrand and Soriano, 1999;Lemay et al, 2015). F0 mutagenesis using CRISPR has recently emerged as a powerful tool in Xenopus and zebrafish, and mosaic crispants generated by targeted injections allow simultaneous observation of wild-type and crispant cellular phenotypes so that observations are automatically staged and synchronized (Aslan et al, 2017;Kakebeen et al, 2020;Kroll et al, 2021;Szenker-Ravi et al, 2018;Willsey et al, 2020).…”
Section: Mosaic Mutation Of Shroom3 Reveals Distinct Anterior and Pos...mentioning
confidence: 99%
“…The differences in cell behaviors we observed between anterior and posterior neural ectodermal regions reflect the region-specific nature of NTDs in both humans and animal models. To explore the relationships in more detail, we next turned to loss-of-function manipulation of shroom3, which is implicated in human NTDs and has variably penetrant effects on anterior and posterior neural tube closure, (Deshwar et al, 2020;Haigo et al, 2003;Hildebrand and Soriano, 1999;Lemay et al, 2015). F0 mutagenesis using CRISPR has recently emerged as a powerful tool in Xenopus and zebrafish, and mosaic crispants generated by targeted injections allow simultaneous observation of wild-type and crispant cellular phenotypes so that observations are automatically staged and synchronized (Aslan et al, 2017;Kakebeen et al, 2020;Kroll et al, 2021;Szenker-Ravi et al, 2018;Willsey et al, 2020).…”
Section: Mosaic Mutation Of Shroom3 Reveals Distinct Anterior and Pos...mentioning
confidence: 99%
“…We found that the genes dysregulated in the DNMT3A KO/+ overlap extensively with the gene sets dysregulated in DNMT3A Baf53b-cKO and MeCP2 mutants ( Figure 6E). For example, all three models show upregulation of Shroom3, whose mutation is associated with developmental defects in humans (Deshwar et al, 2020), and latrophilin-2, a postsynaptic adhesion molecule with roles in synapse targeting and assembly in multiple brain regions (Anderson et al, 2017;Zhang et al, 2020). Shared dysregulation of genes like these in DNMT3A and MeCP2 disorders may contribute to synaptic dysfunction and disease pathology.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore sought to understand how specific changes in cell behavior may explain region-specific NTDs. To this end, we examined the function of the shroom3 gene, which is implicated in human NTDs and has variably penetrant effects on anterior and posterior neural tube closure, with more severe and penetrant anterior defects being observed in both mice and Xenopus (Deshwar et al, 2020; Haigo et al, 2003; Hildebrand and Soriano, 1999; Lemay et al, 2015).…”
Section: Resultsmentioning
confidence: 99%